Pathogenesis of dengue hemorrhagic fever: From immune to genetics - Waidab, Woraman; Suphapeetiporn, Kanya; Thisyakorn, Usa (Journal of Pediatric Infectious Diseases, 2008)
Dengue infection has become one of the most important public health problems worldwide. It can be asymptomatic or cause illnesses ranging from a mild to a severe and sometimes fatal disease. The mechanism underlying disease severity is still not fully understood. Several studies, however, have suggested an immune-mediated process. There are three potential factors contributing to disease severity, including host genetic, virological and epidemiological factors. Recent studies have demonstrated host genetic factors that correlate with susceptibility or resistance to severe dengue infection. Several human leukocyte antigen alleles and non-human leukocyte antigen alleles have been investigated and found to be associated with dengue infection and disease severity. Further studies of genetic risk factors will undoubtedly give important insights into the mechanism of dengue virus pathogenesis leading to the development of more effective strategies for risk assessment, immunotherapy as well as vaccine design.
Keywords: Dengue virus; dengue hemorrhagic fever; risk factors; genetics; polymorphism; pathogenesis